A drug-loaded deformable shape memory stent material and its preparation method and application
Through the preparation and application of drug-loaded deformable shape memory stent materials, the problem of low inflammatory response and implant success rate in bone defect treatment is solved, the drug is sustained and anti-inflammatory effects are achieved, and the microenvironment of the bone injury is improved. , providing new ideas for clinical bone trauma treatment.
Patent Information
- Application Number
- CN202411545233.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-11-01
AI Technical Summary
The existing bone defect treatment methods have problems such as secondary injury, limited resources, infectious disease risk and immune rejection, and it is difficult to effectively solve the difficulty and safety of treatment of large segments of bone defects.
The drug-loaded deformation-deformable shape memory scaffold material is prepared by mixing drug-loaded liposomes, nanosilver modified nanohydroxyapatite suspension and phase change material, and is molded through 3D printing technology and injected into the polyurethane scaffold blank. Perform phase transition treatment to form stent materials with sustained release of drugs, bone-promoting, anti-inflammatory and antioxidant effects.
This material can reduce the inflammatory response during implantation, improve the success rate of implantation, provide drug sustained release and anti-inflammatory effects, improve the microenvironment at bone injury, and is suitable for clinical bone trauma treatment.
Smart Images

Figure CN119034005B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite materials, and in particular to a drug-loaded deformable shape memory stent material and a preparation method and application thereof. Background Art
[0002] With the increase in bone disease patients in an aging society, bone injuries caused by various reasons are difficult to treat and have a high disability rate, which seriously reduces the quality of life of patients and endangers their life safety. Although bones have the ability to regenerate themselves, large bone defects still cannot heal naturally. Clinical methods for treating bone defects include transplantation of autologous bone, allogeneic bone or xenogeneic bone, which have many disadvantages, such as secondary injury, limited resources, risk of infectious diseases and immune rejection. These factors limit their clinical application. Therefore, it is necessary to develop and prepare artificial bones for large bone defects. 3D printing can print biomimetic 3D structures that match biological functional characteristics and have high precision, complex structure and completeness. Because of its scalability, bone defect models of different sizes or geometric shapes can be produced according to the imaging data of different patients, providing better clinical translation applications.
[0003] Bone healing after injury is a complex biomechanical process, and the final healing is highly dependent on the initial inflammatory stage. In the early stage of acute inflammation, cytokines TGF-β, IL-4, and IL-13 produced by immune cells promote osteogenesis (induce osteoblast migration), while cytokines such as TNFα, IL-1, IL-6, and IL-8 inhibit osteogenesis (induce osteoclast activity). Long-term exposure to these cytokines eventually leads to chronic inflammation, causing fibrous encapsulation around the implant material, and ultimately leading to failure of bone integration. Implanted biomaterials can also induce adverse immune reactions such as foreign body reactions (FBR). Foreign body reactions can lead to inflammation, fibrotic encapsulation, tissue damage, and even implant failure. At the same time, long-term use of anti-inflammatory drugs in patients with clinical bone nonunion will produce serious adverse reactions or increase the economic burden on patients and society. Summary of the invention
[0004] In view of this, the purpose of the present invention is to provide a drug-loaded deformable shape memory stent material and its preparation method and application. The drug-loaded deformable shape memory stent material prepared by the present invention can reduce the inflammatory response caused by the implantation of the stent material and improve the implantation success rate.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a drug-loaded deformable shape memory stent material, comprising the following steps:
[0007] The drug-loaded liposome, the nano-silver modified nano-hydroxyapatite suspension and the phase change material are mixed to obtain a mixture; the drug-loaded liposome has a core-shell structure, the core is apigenin-7-O-glucoside, and the shell is liposome;
[0008] Molding the polyurethane material to obtain a polyurethane bracket blank;
[0009] The mixed material is injected into the polyurethane stent blank and then undergoes phase change to obtain a drug-loaded deformable shape memory stent material.
[0010] Preferably, the preparation method of the drug-loaded liposomes comprises the following steps: mixing soybean lecithin, cholesterol, oleic acid, Tween, anhydrous ethanol and apigenin-7-O-glucoside to obtain a mixed solution; injecting the mixed solution into water for emulsification-self-assembly, solid-liquid separation, and the obtained solid component is the drug-loaded liposomes.
[0011] Preferably, the mass ratio of the apigenin-7-O-glucoside to soybean lecithin is 1:0.01-0.5.
[0012] Preferably, the preparation method of the nano-silver modified nano-hydroxyapatite suspension comprises: mixing silver nitrate, water, nano-hydroxyapatite, isopropyl alcohol and glucose, and performing an oxidation-reduction reaction to obtain the nano-silver modified nano-hydroxyapatite suspension.
[0013] Preferably, the mass ratio of the silver nitrate to the nano-hydroxyapatite is 5-20:2-10.
[0014] Preferably, the phase change material comprises a gelatin aqueous solution; the concentration of the gelatin aqueous solution is 5-20wt%;
[0015] The mass of the drug-loaded liposome accounts for 5-30% of the mass of the phase change material.
[0016] Preferably, the molding includes 3D printing molding.
[0017] Preferably, the conditions for the 3D printing molding include: a barrel temperature of 60~200°C, a platform temperature of -2~8°C, an extrusion pressure of 0.4~5 MPa, an extrusion speed of 0.01~5 mm / s, filament advance of 1~100 ms, filament early closing of 1 ms, broken filament elevation of 1~15 mm, the printing model includes a cylindrical type, linear filling is used, the filling spacing is 0.1~10 mm, the number of rotations is 50~200 times, the rotation angle is 15~90°, the number of printing layers is 5~20 layers, and the total thickness is 2~10 mm.
[0018] The present invention provides a drug-loaded deformable shape memory stent material prepared by the preparation method described in the above technical solution.
[0019] The present invention provides the use of the drug-loaded deformable shape memory scaffold material described in the above technical solution in the preparation of bone scaffold materials.
[0020] The invention provides a method for preparing a drug-loaded deformable shape memory scaffold material. The invention uses liposomes to encapsulate apigenin-7-O-glucoside, an important anti-inflammatory monomer of Mongolian medicine blue echinops, to prepare drug-loaded liposomes. The polyurethane material is molded to obtain a polyurethane scaffold blank. A mixture of drug-loaded liposomes, nano-silver modified nano-hydroxyapatite suspension and phase change material is injected into the pores of the polyurethane scaffold blank to prepare a drug-loaded deformable shape memory scaffold material. The drug-loaded deformable shape memory scaffold material prepared by the invention has the effects of drug sustained release, osteogenesis, anti-inflammatory and anti-oxidation. Among them, the polyurethane scaffold blank has a porous topological structure, which is conducive to material exchange; the function of drug sustained release is conducive to the sustained and slow release of drugs; the anti-oxidation effect and anti-inflammatory effect can reduce the ROS expression amount of the microenvironment of artificial bone implant materials, reduce inflammatory cell infiltration, and improve the microenvironment of bone injury, providing a new multifunctional drug-loaded biological bone tissue engineering scaffold treatment for clinical bone trauma treatment. Provide a new idea.
[0021] Furthermore, the preparation method provided by the present invention has simple process, simple operation, low production cost and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 Scanning electron micrograph (left) and particle size distribution (right) of the drug-loaded liposomes prepared in Example 1;
[0023] Figure 2 Transmission electron microscopy image (left) and particle size distribution diagram (right) of nano-silver modified nano-hydroxyapatite prepared in Example 1;
[0024] Figure 3 The actual image (left) and the partial enlarged image (right) of the shape memory polyurethane stent blank of Example 1;
[0025] Figure 4 This is a physical picture of the drug-loaded deformable shape memory stent material prepared in Example 1;
[0026] Figure 5 The drug sustained release kinetic curve of the drug-loaded deformable shape memory stent material prepared in Example 1, wherein A is the standard curve and B is the drug release kinetic curve;
[0027] Figure 6 The effect diagram of the drug-loaded deformable shape memory stent material prepared in Example 1 in removing hydrogen peroxide (left) and hydroxyl radicals (right);
[0028] Figure 7The drug-loaded deformable shape memory scaffold material prepared in Example 1 promotes low expression of interleukin 6 (IL-6) (left) and low expression of tumor necrosis factor (TNF-α) (right);
[0029] Figure 8 The drug-loaded deformable shape memory scaffold material prepared in Example 1 promotes high expression of mannose receptor (CD206) (left) and transforming growth factor-β (TGF-β) (right). DETAILED DESCRIPTION
[0030] The present invention provides a method for preparing a drug-loaded deformable shape memory stent material, comprising the following steps:
[0031] The drug-loaded liposome, the nano-silver modified nano-hydroxyapatite suspension and the phase change material are mixed to obtain a mixture; the drug-loaded liposome has a core-shell structure, the core is vegetative 7-O-glucoside, and the shell is liposome;
[0032] Molding the polyurethane material to obtain a polyurethane bracket blank;
[0033] The mixed material is injected into the polyurethane stent blank and then undergoes phase change to obtain a drug-loaded deformable shape memory stent material.
[0034] Unless otherwise specified, the materials and equipment used in the present invention are all commercially available products in the art.
[0035] The invention mixes drug-loaded liposomes, nano-silver modified nano-hydroxyapatite suspension and phase change material to obtain a mixture; the drug-loaded liposomes have a core-shell structure, the core is vegetative 7-O-glucoside, and the shell is liposomes.
[0036] In the present invention, the source of the apigenin-7-O-glucoside is preferably the Mongolian medicine Echinops edulis. The present invention has no special requirements for the method of extracting apigenin-7-O-glucoside from the Mongolian medicine Echinops edulis, and any extraction method known to those skilled in the art can be used. Apigenin-7-O-glucoside (AG) is the main effective anti-inflammatory ingredient of Echinops edulis.
[0037] In the present invention, the preparation method of the apigenin-7-O-glucoside preferably comprises: mixing Echinops blue powder (dried) with an ethanol solution for extraction to obtain an extract; concentrating the extract to obtain an extract; freeze-drying the extract to obtain a freeze-dried powder; re-dissolving the freeze-dried powder, and separating the obtained freeze-dried powder solution by high performance liquid chromatography-tandem mass spectrometry to obtain apigenin-7-O-glucoside.
[0038] The present invention mixes the blue echinops powder (dried) with an ethanol solution for extraction to obtain an extract. In the present invention, the volume fraction of the ethanol solution is preferably 30-100%, more preferably 50-75%; the amount ratio of the blue echinops powder (dry weight) to the ethanol solution is preferably 1 kg: 1-10 L, more preferably 1 kg: 2-5 L. In the present invention, the extraction temperature is preferably 25-80°C, more preferably 50-60°C; the extraction time is preferably 6-20 h, more preferably 12-20 h; the extraction is preferably carried out under stirring conditions.
[0039] After the extraction is completed, the present invention preferably further comprises performing solid-liquid separation on the obtained extraction system to obtain an extract. The present invention has no particular limitation on the solid-liquid separation, and a solid-liquid separation method well known to those skilled in the art can be used, such as filtration; the purpose of the solid-liquid separation is to remove residues.
[0040] After obtaining the extract, the present invention concentrates the extract to obtain an extract. In the present invention, the concentration preferably includes rotary evaporation; the rotary evaporation temperature is preferably 25-80°C, more preferably 60-80°C; the rotary evaporation time is preferably 2-10 h, more preferably 4-5 h.
[0041] After obtaining the extract, the present invention freeze-dries the extract to obtain freeze-dried powder. The present invention has no particular limitation on the freeze-drying, as long as the solvent can be removed.
[0042] After obtaining the lyophilized powder, the present invention re-dissolves the lyophilized powder, and separates the obtained lyophilized powder solution by high performance liquid chromatography-tandem mass spectrometry to obtain apigenin-7-O-glucoside. In the present invention, the concentration of the lyophilized powder solution is preferably 20-100 mg / mL, more preferably 50-80 mg / mL; the solvent in the lyophilized powder solution preferably includes a lower alcohol aqueous solution, and the volume fraction of the lower alcohol in the lower alcohol aqueous solution is preferably 20-100%, more preferably 30-90%, and further preferably 40-50%; the lower alcohol preferably includes methanol and / or ethanol. In the present invention, the conditions for high performance liquid chromatography-tandem mass spectrometry separation preferably include: high performance liquid chromatography-tandem mass spectrometry separation conditions: separation is performed using a Vanquish UHPLC (ThermoScientific, Waltham, MA) ultra-high performance liquid chromatography system combined with an ACQUITY UPLC HSS T3 (2.1 mm ×100 mm, 1.8 µm) chromatographic column, with a column temperature of 35°C; a flow rate of 0.3 mL / min; mobile phase: mobile phase A is 0.1 v / v% formic acid aqueous solution, and mobile phase B is 0.1 v / v% formic acid-acetonitrile; the elution method is gradient elution, and the gradient elution program is shown in Table 1. The Q-Exactive HFX mass spectrometer was used to collect the primary and secondary spectra of the samples. The Q-Exactive HFX mass spectrometer sample was connected to the UHPLC system. The electrospray ionization (ESI) positive and negative ion modes were used for mass spectrometry acquisition. The spray voltage was 3800V (ESI+) / 3500V (ESI-), the sheath gas pressure was 45arb, the auxiliary gas pressure was 20arb, the ion transfer tube temperature was 320℃, and the nebulization temperature was 350℃. The detection mode was full scan / data-dependent secondary scan (Full-MS / dd-MS2) mode. The primary and secondary resolutions were 60000 and 15000, respectively. The top 10 MS1 ions obtained MS / MS spectra and collision energies (CEs). The step normalization energy levels were 20, 40, and 60; the primary mass-to-charge ratio scanning range was 90~1300. 2 μL of EC-sp solution was accurately aspirated and analyzed by LC-MS injection. The EC-sp sample was injected 5 times.
[0043] Table 1 Gradient elution program
[0044]
[0045] In the present invention, the particle size of the drug-loaded liposome is preferably 250-1000 nm. In the present invention, the preparation method of the drug-loaded liposome preferably comprises the following steps: mixing soybean lecithin, cholesterol, oleic acid, Tween, anhydrous ethanol and apigenin-7-O-glucoside to obtain a mixed solution; injecting the mixed solution into water for emulsification-self-assembly, and obtaining the drug-loaded liposome after solid-liquid separation.
[0046] In the present invention, the mass ratio of the soybean lecithin to cholesterol is preferably 1:0.5~5, specifically preferably 1:0.5, 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5 or 1:5. In the present invention, the dosage ratio of the soybean lecithin to oleic acid is preferably 1 mg:0.05~20 μL, more preferably 1 mg:5~18 μL, and further preferably 1 mg:10~15 μL. In the present invention, the dosage ratio of the soybean lecithin to Tween is preferably 1 mg:0.05~20 μL, more preferably 1 mg:5~18 μL, and further preferably 1 mg:10~15 μL; the Tween preferably includes Tween 80. In the present invention, the dosage ratio of the soybean lecithin to ethanol is preferably 1 mg:0.1~5 mL, and more preferably 1 mg:0.3~0.5 mL. In the present invention, the mass ratio of soybean lecithin to apigenin-7-O-glucoside is preferably 10:0.1-5, specifically preferably 10:0.1, 10:0.5, 10:1, 10:1.5, 10:2, 10:2.5, 10:3, 10:3.5, 10:4, 10:4.5 or 10:5.
[0047] In the present invention, the mixing of soybean lecithin, cholesterol, oleic acid, Tween, ethanol and apigenin-7-O-glucoside preferably comprises: dissolving soybean lecithin, cholesterol, oleic acid and Tween in ethanol and stirring; adding apigenin-7-O-glucoside. In the present invention, the stirring is preferably magnetic stirring; the stirring temperature is preferably 25-100°C, more preferably 40-50°C; the stirring time is preferably 10-60 min, more preferably 20-30 min.
[0048] In the present invention, the volume ratio of the mixed solution to water is preferably 1:1-20, more preferably 1:3-15, and further preferably 1:3-5; the water is preferably deionized water.
[0049] In the present invention, the temperature of the emulsification-self-assembly is preferably room temperature, the time of the emulsification-self-assembly is preferably 15 minutes; and the emulsification-self-assembly is preferably carried out under stirring conditions.
[0050] In the present invention, the solid-liquid separation preferably includes filtration and centrifugal separation in sequence; the pore size of the filter used for the filtration is preferably 70 μm; the centrifugal force of the centrifugal separation is preferably 2000~5000g, more preferably 3000~4000g, and the time of the centrifugal separation is preferably 10~30min, more preferably 10~20min.
[0051] After the solid-liquid separation is completed, the present invention preferably further comprises drying the solid component to obtain drug-loaded liposomes. The present invention has no particular limitation on the drying, and drying to a constant weight is sufficient.
[0052] In the present invention, the structure of the nano-silver modified nano-hydroxyapatite in the nano-silver modified nano-hydroxyapatite suspension is preferably a nanorod structure. In the present invention, the particle size of the nano-silver modified nano-hydroxyapatite is preferably 80-500 nm.
[0053] In the present invention, the method for preparing the nano-silver modified nano-hydroxyapatite suspension preferably comprises: mixing silver nitrate, water, nano-hydroxyapatite, isopropanol and glucose, and performing an oxidation-reduction reaction to obtain the nano-silver modified nano-hydroxyapatite suspension.
[0054] In the present invention, the mass ratio of the silver nitrate to the nano-hydroxyapatite is preferably 5-30:2-20, more preferably 5-20:5-10. In the present invention, the dosage ratio of the nano-hydroxyapatite to isopropanol is preferably 2-20 mg:1 mL, more preferably 5-15 mg:1 mL, and further preferably 10 mg:1 mL; the isopropanol acts as a dispersant. In the present invention, the mass ratio of the silver nitrate to the glucose is preferably 5-30:10-100, more preferably 5-20:50. In the present invention, the glucose is preferably in powder form.
[0055] In the present invention, the mixing of silver nitrate, water, nano-hydroxyapatite, isopropanol and glucose preferably comprises: mixing silver nitrate and part of the water to obtain a silver nitrate solution; mixing glucose and the remaining water to obtain a glucose solution; heating the silver nitrate solution to a temperature for a reduction reaction, and sequentially adding nano-hydroxyapatite, isopropanol and glucose solution. In the present invention, the concentration of the silver nitrate solution is preferably 0.5 to 2 mg / mL, more preferably 1 to 1.5 mg / mL. In the present invention, the concentration of the glucose solution is preferably 50 mg / mL.
[0056] In the present invention, the temperature of the oxidation-reduction reaction is preferably 25-80° C., more preferably 60-80° C.; the time of the oxidation-reduction reaction is preferably 10-120 min, more preferably 30-60 min.
[0057] After the redox reaction is completed, the present invention preferably further comprises: washing the obtained redox reaction system to obtain a nanosilver-hydroxyapatite suspension. In the present invention, the solvent used for the washing preferably comprises water, the water preferably comprises deionized water, and the number of washings is preferably 1 to 4 times, more preferably 2 to 3 times.
[0058] In the present invention, the phase change material preferably comprises a gelatin aqueous solution; the concentration of the gelatin aqueous solution is preferably 5-20wt%, more preferably 10-15wt%. In the present invention, the mass of the drug-loaded liposomes preferably accounts for 5-30% of the mass of the phase change material, more preferably 10-20%, and further preferably 15-20%.
[0059] The invention molds the polyurethane material to obtain the polyurethane bracket blank.
[0060] In the present invention, the polyurethane material preferably includes a shape memory polyurethane material and / or a degradable polyurethane material. The present invention has no special limitation on the polyurethane material, and a commercially available polyurethane material well known to those skilled in the art or a polyurethane material prepared according to an existing method can be used.
[0061] After obtaining the mixture and the polyurethane stent blank, the present invention injects the mixture into the polyurethane stent blank and then phase changes to obtain a drug-loaded deformable shape memory stent material.
[0062] In the present invention, the molding preferably includes 3D printing molding. In the present invention, the conditions for 3D printing preferably include: a barrel temperature of 60 to 200°C, more preferably 100 to 133°C, a platform temperature of -2 to 8°C, more preferably 0 to 2°C, an extrusion pressure of 0.4 to 5 MPa, more preferably 0.6 to 1 MPa, an extrusion speed of 0.01 to 5 mm / s, more preferably 0.1 to 1 mm / s, filament advance of 1 to 100 ms, more preferably 30 to 50 ms, filament advance of 1 ms, broken filament elevation of 1 to 15 mm, more preferably 5 to 10 mm; the printed model is cylindrical, linear filling is used, the filling spacing is 0.1 to 10 mm, more preferably 1 to 3 mm, the number of rotations is 50 to 200 times, more preferably 88 to 100 times, the rotation angle is 15 to 90°, more preferably 70 to 90°; the number of printed layers is 5 to 20 layers, more preferably 10 to 15 layers, and the total thickness is 2 to 10 mm, more preferably 5 to 8 mm.
[0063] The present invention utilizes biological 3D printing technology to print out a model that matches the size and shape of the defect, thereby solving the problem of poor treatment effect of large bone defects with or without irregular shapes.
[0064] The present invention provides a drug-loaded deformable shape memory stent material prepared by the preparation method described in the above technical solution. In the present invention, the drug-loaded deformable shape memory stent material comprises drug-loaded liposomes, nano-silver modified nano-hydroxyapatite and polyurethane material.
[0065] The present invention provides the use of the drug-loaded deformable shape memory scaffold material described in the above technical solution in the preparation of bone scaffold materials.
[0066] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0067] Example 1
[0068] Preparation of drug-loaded liposomes:
[0069] 1 kg of dried Echinops cyanobacteria powder was mixed with 2 L of 75 wt% ethanol, heated to 60°C with mechanical stirring, extracted for 12 hours, filtered, and the residue was removed. The filtrate was rotary evaporated at 80°C for 4 hours to evaporate the ethanol to obtain a drug extract, which was frozen at -20°C for 12 hours and freeze-dried in a freeze dryer for 48 to 72 hours to obtain a lyophilized powder. The lyophilized powder was dissolved in a 40v / v% methanol aqueous solution, vortexed for 30 seconds, centrifuged at 16000 g and 4°C for 15 minutes, and the supernatant was a lyophilized powder solution. The lyophilized powder solution was separated by high performance liquid chromatography-tandem mass spectrometry to obtain apigenin-7-O-glucoside. The solid-liquid ratio of the lyophilized powder to the methanol aqueous solution was 20 mg: 0.3 mL.
[0070] HPLC-MS / MS separation conditions: Vanquish UHPLC (Thermo Scientific, Waltham, MA) ultra-high performance liquid chromatography system combined with ACQUITY UPLC HSS T3 (2.1 mm × 100 mm, 1.8 µm) column was used for separation. The column temperature was 35 °C. The flow rate was 0.3 mL / min. The mobile phases were: mobile phase A was 0.1 v / v% formic acid in water, and mobile phase B was 0.1 v / v% formic acid-acetonitrile. The elution mode was gradient elution. The gradient elution program is shown in Table 1. The Q-Exactive HFX mass spectrometer was used to collect the primary and secondary spectra of the samples. The Q-Exactive HFX mass spectrometer sample was connected to the UHPLC system. The electrospray ionization (ESI) positive and negative ion modes were used for mass spectrometry acquisition. The spray voltage was 3800V (ESI+) / 3500V (ESI-), the sheath gas pressure was 45arb, the auxiliary gas pressure was 20arb, the ion transfer tube temperature was 320℃, and the nebulization temperature was 350℃. The detection mode was full scan / data-dependent secondary scan (Full-MS / dd-MS2) mode. The primary and secondary resolutions were 60000 and 15000, respectively. The top 10 MS1 ions obtained MS / MS spectra and collision energies (CEs). The step normalization energy levels were 20, 40, and 60; the primary mass-to-charge ratio scanning range was 90~1300. 2 μL of EC-sp solution was accurately aspirated and analyzed by LC-MS injection. The EC-sp sample was injected 5 times.
[0071] 10 mg soybean lecithin, 5 mg cholesterol, 150 μL oleic acid, and 150 μL Tween 80 were dissolved in 3 mL anhydrous ethanol, and stirred magnetically at 50°C for 30 min; 1 mg apigenin-7-O-glucoside was added and mixed to obtain a mixed solution; the mixed solution was slowly injected into 10 mL deionized water using a 1 mL syringe, and stirred magnetically for 15 min, and filtered through a 70 μm filter. The obtained solid component was centrifuged at 3000g for 10 min and dried to constant weight to obtain drug-loaded liposomes. Figure 1 The SEM image (left) and particle size distribution diagram (right) of the drug-loaded liposomes show that the drug-loaded liposomes are microspherical with a particle size of 250~1000 nm.
[0072] Preparation of Nano-Silver Modified Nano-Hydroxyapatite Suspension
[0073] Dissolve 20 mg of silver nitrate in 10 mL of deionized water and stir magnetically for 30 min; heat to 80°C, add 10 mg of nano-hydroxyapatite, continue stirring, add 1 mL of isopropanol, and continue stirring for 10 min; dissolve 50 mg of glucose powder in 1 mL of deionized water, add to the mixed solution after it is fully dissolved, continue stirring for 60 min, and wash with deionized water twice to obtain a nano-silver modified nano-hydroxyapatite suspension. Figure 2 The transmission electron microscope image (left) and particle size distribution diagram (right) of nano-silver modified nano-hydroxyapatite show that the particle size of nano-silver modified nano-hydroxyapatite is 80~500 nm.
[0074] Preparation of shape memory polyurethane scaffold blank by 3D printing
[0075] 10 g of polyurethane powder with shape memory function was placed in a barrel, and a high-temperature printing nozzle with a diameter of 400 µm was selected to complete the barrel loading; it was installed on the mechanical arm of the 3D bioprinter, the nozzle temperature was set to 133°C, the platform temperature was set to 21°C, the extrusion pressure was 0.8 MPa, the extrusion speed was 0.1 mm / s, the wire was advanced by 50 ms, the wire was closed by 1 ms, and the broken wire was raised by 15 mm; the printed model was cylindrical, linear filling was used, the filling spacing was 1 mm, the number of rotations was 88 times, and the rotation angle was 90°; the shape memory polyurethane scaffold blank was obtained by 3D printing, Figure 3 The actual picture (left) and the partial enlarged picture (right) of the prepared shape memory polyurethane bracket material blank show that the prepared shape memory polyurethane bracket material blank has a porous structure.
[0076] Preparation of drug-loaded deformable shape memory stent materials:
[0077] 200 mg of the drug-loaded liposomes, 100 mg of the nano-silver-modified nano-hydroxyapatite suspension and 1 g of 10 wt% gelatin aqueous solution were uniformly mixed at 80° C. The resulting mixture was loaded into the pores of the shape memory polyurethane stent blank, cooled at 4° C., frozen at -20° C. for 4 h, and freeze-dried in a freeze dryer for 48 h to obtain a drug-loaded deformable shape memory stent material. Figure 4 This is a physical picture of the prepared drug-loaded deformable shape memory stent material.
[0078] Test Example 1
[0079] Drug sustained release kinetics test of drug-loaded deformable shape memory stent material
[0080] The drug-loaded deformable shape memory stent material was placed in physiological saline, and samples were taken at 1, 4, 8, 24, 48 and 72 h, respectively. The absorption peak was detected by ultraviolet spectrophotometer at 268 nm, and a standard curve was drawn, as shown in FIG. Figure 5As shown in A, the content of apigenin-7-O-glucoside released from the drug-loaded deformable shape memory stent material at different time points was calculated, and the drug release kinetic curve was drawn, as shown in Figure 5 As shown in B. Figure 5 From Figure B, we can see that 0~4h is the burst release phase of the drug apigenin-7-O-glucoside, and 8~72h is the sustained release phase of the drug.
[0081] Test Example 2
[0082] Drug-loaded deformable shape memory stent material scavenges hydrogen peroxide and hydroxyl radicals
[0083] The drug-loaded deformable shape memory scaffold material was completely immersed in saline at 37°C, and the extracts were collected after 1, 12, 24, 48, and 72 hours. The extracts were mixed with hydrogen peroxide (H 2 O 2 ) and hydroxyl radicals (•OH) were incubated for 30 min, and •OH and H 2 O 2 Kit staining to evaluate the removal of OH and H by the extract 2 O 2 The content of Figure 6 As shown in FIG. 1 , it can be seen that the drug-loaded deformable shape memory stent material prepared by the present invention has good H removal performance. 2 O 2 and hydroxyl radicals •OH, and is concentration-dependent.
[0084] Test Example 3
[0085] Anti-inflammatory effect of drug-loaded deformable shape memory scaffold materials
[0086] Mouse mononuclear macrophage leukemia cells (RAW 264.7) were stimulated with lipopolysaccharide (LPS) to highly express interleukin 6 (IL-6) and tumor necrosis factor (TNF-α) and other inflammatory factors. The extracts of drug-loaded deformable shape memory scaffolds were added to the LPS-stimulated RAW264.7 cells for 24, 48 and 72 h, respectively, and the effects of the extracts on the expression of IL-6, TNF-α, CD206 and TGF-β in RAW 264.7 cells were evaluated after culturing at 37℃ for 24 h. Figure 7 The image of the drug-loaded deformable shape memory scaffold material extract promoting low expression of IL-6 (left) and TNF-α (right). Figure 8 The extract of drug-loaded deformable shape memory scaffold material promotes high expression of CD206 (left) and TGF-β (right). Figure 7 and Figure 8It can be seen that the drug-loaded deformable shape memory stent material prepared by the present invention has a good anti-inflammatory effect.
[0087] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a drug-loaded deformable shape memory stent material, comprising the following steps: The drug-loaded liposome, nano-silver modified nano-hydroxyapatite suspension and phase change material are mixed to obtain a mixture; the drug-loaded liposome has a core-shell structure, the core is apigenin-7-O-glucoside, the shell is liposome, and the particle size of the drug-loaded liposome is 250-1000 nm; in the preparation process of the drug-loaded liposome, the mass ratio of apigenin-7-O-glucoside to soybean lecithin is 1:0.01-0.5; in the preparation process of the nano-silver modified nano-hydroxyapatite suspension, the mass ratio of silver nitrate to nano-hydroxyapatite is 5-20:2-10; the phase change material includes gelatin aqueous solution; the concentration of the gelatin aqueous solution is 5-20wt%; the mass of the drug-loaded liposome accounts for 5-30% of the mass of the phase change material; Molding the polyurethane material to obtain a polyurethane bracket blank; the molding includes 3D printing molding; The mixed material is injected into the polyurethane stent blank and then undergoes phase change to obtain a drug-loaded deformable shape memory stent material.
2. The preparation method according to claim 1, characterized in that: The preparation method of the drug-loaded liposome comprises the following steps: mixing soybean lecithin, cholesterol, oleic acid, Tween, anhydrous ethanol and apigenin-7-O-glucoside to obtain a mixed solution; injecting the mixed solution into water for emulsification-self-assembly, solid-liquid separation, and obtaining a solid component as the drug-loaded liposome.
3. The preparation method according to claim 1, characterized in that: The preparation method of the nano-silver modified nano-hydroxyapatite suspension comprises: mixing silver nitrate, water, nano-hydroxyapatite, isopropanol and glucose, and performing redox reaction to obtain the nano-silver modified nano-hydroxyapatite suspension.
4. The preparation method according to claim 1, characterized in that: The 3D printing molding conditions include: a barrel temperature of 60~200°C, a platform temperature of -2~8°C, an extrusion pressure of 0.4~5 MPa, an extrusion speed of 0.01~5 mm / s, filament advance of 1~100 ms, filament shutdown in advance of 1 ms, broken filament elevation of 1~15 mm, a printed model including a cylindrical type, linear filling, a filling spacing of 0.1~10 mm, a rotation number of 50~200 times, a rotation angle of 15~90°, a printing number of layers of 5~20, and a total thickness of 2~10 mm.
5. The drug-loaded deformable shape memory stent material prepared by the preparation method according to any one of claims 1 to 4.
6. Use of the drug-loaded deformable shape memory scaffold material according to claim 5 in the preparation of bone scaffold materials.
Citation Information
Patent Citations
Peanut oil membrane protein modified liposome and preparation method thereof
CN112957266A
ID2018S01062A